Carbohydrate and lipid status in soybean roots influenced by ferulic acid uptake - Lucio Ferrarese, Maria de Lourdes; De Souza, Nilson Evlázio; Rodrigues, João Domingos [UNESP]; Ferrarese-Filho, Osvaldo (Springer Nature, 2001)
The objective of this research was to investigate how the allelochemical ferulic acid affects the carbohydrate and lipid contents of soybean roots cultivated in nutrient culture. The results presented revealed that ferulic acid has significant effects on carbohydrates by the increase in xylose, fructose and sucrose and decrease in glucose, after 24 h treatment of roots. Ferulic acid increased the contents of saturated and unsaturated fatty acids of the polar and non-polar lipid fractions. The results may contribute as additional data to explain allelopathic effects caused by ferulic acid.
Keywords: Carbohydrate; Fatty acids; Ferulic acid; Glycine max L. Merr.; Roots; Soybean; Glycine max